Application of microcrystalline glass in optical fiber ferrule and optical fiber connector

By using improved formula microcrystalline glass to prepare optical fiber ferrules, the problems of dimensional instability and impaired transmission performance of optical fiber ferrugated cores in the prior art under extreme high temperature environments and thermal cycling impacts are solved, and higher environmental stability and thermal shock resistance are achieved, and the application scope is expanded.

CN119612964APending Publication Date: 2025-03-14YANGTZE OPTICAL FIBRE & CABLE CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411794461.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing fiber ferrules have unstable dimensions and damaged transmission performance under extreme high temperature environments and thermal cycling impacts, and the extreme environmental stability and thermal shock resistance of zirconia ceramic ferrules are insufficient.

Method used

The improved formula microcrystalline glass is used as the optical fiber ferrule material, including 50 wt%~80 wt% SiO2, 5 wt%~40 wt% Al2O3, 8 wt%~30 wt% Li2O and 0.1 wt%~3 wt% strength additives, and is prepared by sintering or overall crystallization method to form a microcrystalline glass ferrule with low thermal expansion coefficient, high mechanical strength and good thermal shock resistance.

Benefits of technology

The environmental stability and thermal shock resistance of fiber optic connectors in extremely high temperature environments have been improved, the performance fluctuations caused by high-temperature thermal expansion and thermal cycling impact have been reduced, and the application range has been expanded to high-temperature fields such as high-power lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612964A_ABST
    Figure CN119612964A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of optical fibers, and particularly discloses application of microcrystalline glass in an optical fiber ferrule and an optical fiber connector. The glass ceramic comprises the following components in percentage by weight: 50 to 80 percent of SiO2 (silicon dioxide), 5 to 40 percent of Al2O3 (aluminum oxide), 8 to 30 percent of Li2O (lithium oxide) and 0.1 to 3 percent of a strength additive, the strength additive is one or more of a rare earth metal compound, a transition metal compound, organic fibers, borate, phosphate, magnesium oxide or magnesium fluoride. According to the invention, the microcrystalline glass added with the strength additive is used as an insertion core material of the optical fiber connector, so that the optical fiber connector can show higher environmental stability and higher thermal shock resistance in an extremely high temperature environment, and performance fluctuation caused by high temperature thermal expansion and thermal cycle impact is reduced; and the method can be applied to high-temperature fields such as high-power laser and the like and fields with large environment temperature change.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of optical fiber technology, and more specifically, relates to an application of microcrystalline glass in optical fiber ferrules and optical fiber connectors. Background Art

[0002] High-speed optical networks require a large number of fiber optic connectors, which are mainly used to achieve non-permanent fixed connections between devices, between devices and instruments, between devices and optical fibers, and between optical fibers in the system. Fiber optic connectors are the most common and widely used basic passive components in optical communication systems. Their stability and precision directly affect the quality of communication. The fiber optic ferrule is one of the core components of the fiber optic connector. It has microholes inside to fix the optical fiber. The quality of the fiber optic ferrule has an important impact on the signal loss on the optical fiber link. In order to achieve accurate transmission of optical signals at the optical fiber connector, stringent requirements are placed on the ferrule material in the optical fiber connector: (1) The optical fiber should be able to easily pass through the microhole of the ferrule; (2) The core material should be able to achieve high machining accuracy, especially the machining accuracy of inner diameter, outer diameter and concentricity; (3) The core material should have sufficient strength and wear resistance, and should not fail during installation, disassembly and use, and should not break when subjected to accidental impact; (4) The core material should have a thermal expansion coefficient similar to that of the optical fiber (5×10 -6 / ℃), when the ambient temperature changes, the contraction and expansion of the ferrule are basically the same as the optical fiber, so as to ensure the close contact of the optical fiber end face and prevent the loss of optical signal; (5) The core material also needs to have good high temperature environment stability and thermal shock resistance to adapt to applications in extreme high temperature environments, thermal cycle shock and other environments.

[0003] Fiber optic ferrules are mainly classified by material into ceramic ferrules, plastic ferrules, metal ferrules, and glass ferrules. Plastic ferrules have poor heat resistance, chemical resistance, and dimensional stability, insufficient wear resistance, and easy aging. Metal ferrules have problems such as high manufacturing cost and easy corrosion. Zirconia ceramic ferrules have high strength and hardness, and have the characteristics of high processing accuracy, wear resistance, long service life, low insertion loss, and high return loss. They are currently the most widely used type of fiber optic ferrule material. However, zirconia ceramic ferrules have poor extreme environmental stability, poor thermal shock resistance, and high sintering and processing costs. Its thermal expansion coefficient is about 8.3×10 -6 / ℃, in some extreme environments, such as extreme high temperatures in the laser field, continuous laser action and other extreme conditions, the difference in thermal expansion coefficients between zirconia ceramics and other materials such as optical fibers will lead to thermal stress concentration; at the same time, zirconia ceramics will transform from monoclinic phase to tetragonal phase (high temperature stable phase) in high temperature environment. This transformation process will be accompanied by an increase in volume and increase in thermal stress, and will transform in the opposite direction when cooled, accompanied by a decrease in volume, which will cause the instability of the performance of optical fiber connectors and a reduction in service life, which seriously restricts its application as an optical fiber core material in extreme environments. In addition, zirconia ceramics have poor thermal shock resistance. When the ambient temperature rises or drops rapidly, the core is prone to instantaneous fracture; under the impact of high temperature cycles, the core is prone to cracking. Therefore, its application in extreme high temperature environments and thermal cycle shock conditions is limited.

[0004] Conventional glass ferrules have good chemical stability, thermal shock resistance, good thermal matching performance with optical fibers, and strong environmental stability, so they are widely studied. However, conventional glass ferrules have poor processing accuracy, brittle materials, and low strength, which also have disadvantages in application. With the continuous development of glass materials, microcrystalline glass with high strength and wear resistance, low thermal expansion coefficient, and good resistance to thermal shock damage has become an ideal alternative material for zirconia ceramic ferrules and conventional glass ferrules.

[0005] The non-patent document "High-Strength Glass-Ceramic Ferrule for SC-Type Single-Mode Optical Fiber Connector" (IEEE PHOTONICS TECHNOLOGY LETTERS, VOL. 9, NO.11,1502-1504) discloses the use of LAS-based microcrystalline glass as the SC-type single-mode optical fiber connector ferrule. The prepared microcrystalline glass has a bending strength of about 500MPa. After a sandpaper scratch test, its bending strength is reduced from 502Mpa to 310Mpa. However, microcrystalline glass has the disadvantages of instability in high temperature environments and poor thermal shock resistance, which affects its use effect and service life as an optical fiber connector ferrule in extreme environments.

[0006] Japanese patent JPH08171030A discloses the use of a material with an inner layer of silicate glass and an outer layer of microcrystalline glass or part of microcrystalline glass as the ferrule of the optical fiber connector, and the formation of a compressive stress layer on the contact surface of the two through ion exchange. The preparation method of the ferrule is: integrating silicate glass with a longitudinal through hole and glass with a microcrystalline glass component and performing precision processing, forming the required diameter of the optical fiber ferrule through a wire drawing process, and then forming microcrystalline glass on the outer layer through a crystallization treatment at 1200°C. The prepared optical fiber ferrule has the advantages of high surface processing accuracy and high mechanical strength (165MPa~1107MPa), and strong weather resistance of 40°C~85°C. However, the core material of this patent uses a nested structure of silicate glass and microcrystalline glass, which requires internal drilling and precision processing of the integrated glass. Therefore, the processing cost is high and it is difficult to ensure the concentricity and inner and outer diameter tolerances of the optical fiber core. In addition, due to the inconsistent melting points of the inner layer of silicate glass and the outer layer of microcrystalline glass, the high-temperature melt drawing process may cause the separation of the inner and outer layers of the material, and will not produce a tight bond, which will affect the performance of the core. At the same time, the weather resistance cannot meet the use requirements in extreme environments with greater temperature differences. Summary of the invention

[0007] In view of the defects of the prior art, the purpose of this application is to apply microcrystalline glass with an improved formula to optical fiber ferrules to replace the nesting process of optical fiber ferrules, without using costly processing technology, to overcome the shortcomings of microcrystalline glass itself, such as difficulty in maintaining stability and thermal shock resistance in extreme environments, and to solve the problems of dimensional instability and impaired transmission performance of optical fiber ferrules and their connectors under extreme high temperature environments and thermal cycle shock.

[0008] To achieve the above-mentioned objectives, in one aspect, the present application provides an application of microcrystalline glass in an optical fiber ferrule, wherein the microcrystalline glass includes 50 wt%~80wt% of SiO2, 5wt%~40wt% of Al2O3, 8wt%~30wt% of Li2O and 0.1wt%~3wt% of a strength additive; the strength additive is one or more of a rare earth metal compound, a transition metal compound, an organic fiber, a silicon nitride fiber, a borate, a phosphate, magnesium oxide or magnesium fluoride.

[0009] Preferably, the strength additive is ZnO or MgO.

[0010] Preferably, the microcrystalline glass also includes 0.5 wt% to 7wt% of a crystal nucleating agent, 0wt% to 3wt% of a clarifier and 1wt% to 6wt% of a flux.

[0011] As a further preference, the nucleating agent is one or more of ZrO2, TiO2, P2O5, SnO2, and Nb2O5.

[0012] As further preferred, the clarifier is one or more of Na2SO4, Sb2O3, and SnO2.

[0013] As further preferred, the flux is one or more of Na2O, MgO, K2O, B2O3, and ZnO.

[0014] Preferably, the thermal expansion coefficient of the optical fiber ferrule is less than 5×10 -6 / ℃, the maximum allowable temperature difference is greater than 600℃.

[0015] Preferably, the glass-ceramics is prepared by a sintering method or a bulk crystallization method.

[0016] In another aspect, the present application also provides an optical fiber ferrule, the material of the optical fiber ferrule is microcrystalline glass, the microcrystalline glass includes 50 wt%~80wt% SiO2, 5wt%~40wt% Al2O3, 8wt%~30wt% Li2O and 0.1wt%~3wt% strength additives; the strength additive is one or more of rare earth metal compounds, transition metal compounds, organic fibers, silicon nitride fibers, borates, phosphates, magnesium oxide, and magnesium fluoride.

[0017] In another aspect, the present application also provides a fiber optic connector including the above-mentioned fiber optic ferrule.

[0018] Preferably, the optical fiber connector is an LC type, SC type, ST type, FC type, MU type or MTRJ type optical fiber connector.

[0019] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: 1. This application uses microcrystalline glass with added strength additives as the core material of the optical fiber connector, which can make the optical fiber connector of this application show higher environmental stability and stronger thermal shock resistance in extreme high temperature environments, reduce the performance fluctuation caused by high temperature thermal expansion and thermal cycle shock, and can be expanded to high-temperature fields such as high-power lasers and fields with large ambient temperature changes; 2. The microcrystalline glass has a low thermal expansion coefficient and good mechanical processing performance, which is suitable for precise docking and stable transmission of optical fiber connectors; 3. By properly adding flux, nucleating agent, clarifier, etc. to the glass-ceramics, the glass-ceramics can form a more uniform and dense microstructure and form more microcrystalline phases, thereby enhancing the wear resistance and strength of the glass-ceramics; 4. The preparation process of glass-ceramics is relatively complicated compared with zirconia ceramics, but because its density and hardness are lower than zirconia ceramics, it is easier to process, so the processing cost is low; if mass-produced and used, it can be made at a lower cost; at the same time, its advantages in long-term stability and durability can significantly reduce the maintenance cost and replacement frequency of optical fiber connectors; 5. The optical fiber connector of the present application can be widely used in the fields of high-power laser, communication, energy, transportation, aerospace, etc., especially in the occasions with high requirements on extreme environmental stability, thermal shock resistance and precision. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the preparation process of Example 1 of the present application; Figure 2 This is a schematic diagram of the preparation process of Example 2 of the present application; Figure 3 This is a schematic diagram of the cross-sectional structure of the microcrystalline glass insert provided in an embodiment of the present application: the leftmost one is the PC (Physical Contact) type, the middle one is the UPC (Ultra Physical Contact) type, and the right one is the APC (Angled-Physical Contact) type. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0022] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the feature. In the description of the present application, "plurality" means two or more, unless otherwise clearly and specifically defined.

[0023] In addition, references throughout this specification to "one embodiment"; "one embodiment", "an example" or similar language indicate that a particular feature, structure, or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present application. Thus, appearances of the phrase "in one embodiment"; "in one embodiment" and similar language throughout this specification may, but do not necessarily, all refer to the same embodiment.

[0024] In order to further improve the extreme environmental stability and thermal shock resistance of optical fiber connectors, the present application addresses the shortcomings of ceramic ferrules widely used in existing optical fiber connectors and provides a microcrystalline glass optical fiber ferrule that uses a low expansion coefficient lithium aluminum silicon glass as a raw material and is processed into a microcrystalline glass optical fiber ferrule with good chemical stability, low processing cost, high precision, and strong resistance to thermal shock damage, which can replace traditional zirconia ceramic ferrules in optical fiber connectors.

[0025] The microcrystalline glass in the optical fiber ferrule includes 50 wt%~80wt% of SiO2, 5wt%~40wt% of Al2O3, 8wt%~30wt% of Li2O, 0.5 wt%~7wt% of a nucleating agent, 0 wt%~3wt% of a clarifying agent, 1wt%~6wt% of a flux and 0.1wt%~3wt% of a strength additive; in some embodiments, the content of SiO2 is 50 wt%~70wt%, the content of Al2O3 is 6 wt%~25wt%, the content of Li2O is 14 wt%~15wt%, the content of the nucleating agent is 1.9wt%~6wt%, the content of the clarifying agent is 1wt%~2wt%, and the content of the flux is 2.4wt%~6wt%.

[0026] Among them, the nucleating agent is one or more of ZrO2, TiO2, P2O5, SnO2, and Nb2O5; the clarifier is one or more of Na2SO4, Sb2O3, and SnO2; the flux is one or more of Na2O, MgO, K2O, B2O3, and ZnO; the strength additive is one or more of rare earth metal compounds, transition metal compounds (such as ZrO2, ZnO, and Al2O3), high-strength organic fibers (such as C, SiC), or Si3N4 fibers, borates, phosphates, magnesium oxide, or magnesium fluoride, so as to increase the strength and toughness of the microcrystalline glass; since some of the components (such as flux and strength additives) can function as one substance, when a certain substance has the functions of two components, calculation based on the functional components may make the total mass fraction of the microcrystalline glass exceed 100%.

[0027] In other embodiments, the nucleating agent is ZrO2, TiO2 or P2O5, the clarifying agent is SnO2 or Sb2O3, the fluxing agent is MgO, K2O or Na2O, and the strength additive is ZnO and / or MgO; wherein ZnO can enhance the stability of the glass network and reduce the mobility of ions in the glass, thereby resisting the erosion of the external environment and deformation under high temperature; the addition of MgO can reduce the crystallization temperature of LAS glass-ceramics, so that the crystal can start to grow at a lower temperature; at the same time, the strength of LAS glass-ceramics is increased. The crystallinity of LAS microcrystalline glass increases, making the crystals more perfect, thereby improving its strength and hardness; in addition, the addition of MgO can also promote the precipitation of specific crystalline phases (such as diopside, forsterite, etc.), and the formation of these crystalline phases further enhances the mechanical properties of LAS microcrystalline glass, such as flexural strength and compressive strength; when ZnO and MgO are used as strength additives at the same time, ZnO replacing part of MgO can improve the overall crystallinity, improve the strength and hardness of microcrystalline glass, and help form more stable and finer grains, thereby enhancing the microstructure of microcrystalline glass.

[0028] In some embodiments, the glass-ceramics are prepared by a sintering method or a bulk crystallization method. The two process flow charts are as follows: Figure 1 , Figure 2 As shown. Among them, high temperature sintering, heat treatment temperature and time can be adjusted according to specific formula and performance requirements.

[0029] The steps of preparing the glass-ceramic ferrule by sintering method are as follows: S1. Raw material preparation: Select appropriate amounts of silicon oxide, aluminum oxide, lithium oxide, etc. as glass raw material components, add appropriate amounts of nucleating agents, a small amount of clarifiers, fluxing agents and strength additives, and ensure that the raw materials are mixed evenly.

[0030] S2. Melt molding: Put the prepared raw materials into a high-temperature furnace for high-temperature melting, so that the raw materials are completely melted to form a uniform glass liquid. The glass liquid is quenched with water and dried, and then ball-milled in a ball mill to obtain powder. Then, an adhesive is added, and the mixture is placed in a mold for pressing or injection molding to obtain the initial shape of the optical fiber ferrule.

[0031] S3. High temperature sintering: The initially formed optical fiber ferrule is sintered at high temperature to form a microcrystalline glass ferrule with the required properties.

[0032] The steps for preparing the glass-ceramic insert by the overall crystallization method (i.e., high-temperature melting method) are as follows: S1. Raw material selection and preparation: Select appropriate amounts of silicon oxide, aluminum oxide, lithium oxide, etc. as glass raw material components, add appropriate amounts of nucleating agents, a small amount of clarifiers, fluxing agents and strength additives to ensure the purity and accurate proportion of the raw materials.

[0033] S2. Melt molding: Put the prepared raw materials into a high-temperature furnace and heat them to the melting temperature to completely melt the raw materials to form a uniform glass liquid. Subsequently, the preliminary shape of the optical fiber ferrule is obtained by casting or pressing through a precision mold. In this process, the melting temperature and holding time must be strictly controlled to ensure the uniformity and fluidity of the glass liquid.

[0034] S3. Overall crystallization treatment: The initially formed optical fiber ferrule is placed in a heat treatment furnace for overall crystallization treatment. This process includes two stages: nucleation treatment and crystallization treatment. Nucleation treatment is to form a large number of crystal nuclei inside the glass at a lower temperature; crystallization treatment is to grow the crystal nuclei into fine crystal phases at a higher temperature to form a microcrystalline glass ferrule with the required properties. By precisely controlling parameters such as heat treatment temperature, holding time and cooling rate, the overall uniform crystallization of the glass material can be achieved.

[0035] After the microcrystalline glass blank is obtained by the above method, it is then precisely ground and polished to remove surface defects and tiny cracks to ensure that its dimensional accuracy and surface finish meet the design requirements of the optical fiber connector. High-precision grinders and polishing equipment are used during the processing to ensure processing quality and ensure that the optical fiber can be connected with low loss.

[0036] The "mutual flipping" of the Si and Al tetrahedral structures in this material produces a shearing effect on the crystal, changing the oxygen coordination of Si (from tetrahedron to octahedron), reducing the elastic constant, thereby achieving low thermal expansion or even negative expansion. When the temperature changes, the volume of the material changes little, and the thermal stress generated is also small. At the same time, the composite effect of its microcrystalline structure and glass phase enables the material to absorb and disperse stress when the temperature changes, and can still maintain good integrity under rapidly changing temperature conditions and is not easy to crack. Among them, the addition of strength additives can achieve induced grain refinement, stress-induced phase transformation toughening, microcrack toughening, or form composite material toughening with microcrystalline glass.

[0037] It has been verified that the microcrystalline glass optical fiber ferrule prepared according to the formula ratio in the method of this application has an inner diameter tolerance of ≤0.3μm, an outer diameter tolerance of ≤0.3μm, a concentricity of ≤0.5μm, and a bending strength of ≥400MPa. The optical fiber connector ferrule is subjected to thermal shock cycle and thermal shock resistance tests, and its maximum allowable temperature difference is ≥600℃, and its thermal shock resistance and extreme environmental stability are strong. The microcrystalline glass ferrule has a low thermal expansion coefficient matching the optical fiber material, good corrosion resistance, extreme environmental stability and thermal shock resistance, and is an ideal optical fiber connector ferrule material.

[0038] The maximum allowable temperature difference △T is an evaluation index of thermal shock resistance, and its calculation formula is as follows: ΔT=△T1+((10%- δ 1 * ) / ( δ 2 * - δ 1 * ))×(ΔT2-ΔT1) ΔT: The maximum thermal shock temperature difference corresponding to a 10% attenuation rate of the bending strength after the thermal shock test. △T1 and △T2: The temperature difference between the test temperatures T1 and T2 and the cooling medium when the attenuation rate of the bending strength at two adjacent test temperatures T1 and T2 is less than 10% and greater than 10% and less than 20%, respectively.

[0039] δ 1 * and δ 2 * : Bending strength attenuation rate at test temperatures T1 and T2.

[0040] The optical fiber ferrule can be used for LC (Lucent Connector), SC (Subscriber Cable or Square Connector), ST (Stab & Twist or Straight Tip), FC (Ferrule Connector), MU (Miniature Unit Coupling) or MTRJ (Miniature Tri-Conexor) optical fiber connectors; the optical fiber connector also includes other components for fixing the optical fiber, such as a positioning mechanism and a locking mechanism, which are used to ensure the precise position and stable connection of the optical fiber in the ferrule. The optical fiber connector can achieve high-precision, low-loss connection between optical fibers.

[0041] When connecting, assemble the processed microcrystalline glass fiber ferrule with the optical fiber and other components into a fiber optic connector. Insert the pre-processed optical fiber into the hole of the microcrystalline glass ferrule to ensure that the optical fiber and the ferrule are coaxial and the end faces are in close contact. Then, fix the ferrule in the sleeve and install springs and other fixing devices at both ends of the sleeve to ensure the precise docking and fixation of the optical fiber and ensure that the insertion loss and return loss of the optical fiber connector meet the communication requirements.

[0042] On the basis of the above technical solution, the assembled connector ferrule end is ground, including multiple steps such as coarse grinding, fine grinding, fine grinding and polishing, and can be ground into three end face contact modes: PC, UPC and APC.

[0043] The following are examples: Example 1 Preparation of glass-ceramic core by sintering method The preparation process of this embodiment is as follows Figure 1 As shown, the details are as follows: (1) Raw material preparation Select appropriate amounts of SiO2, Al2O3, Li2O, etc. as glass formers, among which the SiO2 content is 70wt%, the Al2O3 content is 6wt%, and the Li2O content is 14wt%; add 5wt% ZrO2 and 1wt% TiO2 as nucleating agents, 1wt% Sb2O3 as a clarifier, 2.4wt% MgO as a flux and strength additive, and 0.6wt% ZnO as a flux and strength additive to ensure that the above raw materials are mixed evenly.

[0044] (2) Melt molding The prepared raw materials are placed in a high temperature furnace for high temperature melting at 1550℃±5℃ to completely melt the raw materials into a uniform glass liquid. The glass liquid is water quenched and dried, and then ball milled in a ball mill to obtain powder. Then, an adhesive is added, and the powder is placed in a mold for pressing or injection molding to obtain the initial shape of the plug.

[0045] (3) High temperature sintering The initially formed core is sintered at 1000°C ± 5°C for 2 hours to form a glass-ceramic core with the required properties.

[0046] (4) Precision machining The ferrule after high-temperature sintering is precisely ground and polished to remove surface defects and tiny cracks to ensure that its dimensional accuracy meets the requirements.

[0047] (5) Performance testing The prepared microcrystalline glass optical fiber ferrule was tested. The outer diameter of the ferrule was 2.499±0.0003mm, the outer diameter tolerance was ≤0.3μm, the inner diameter was 0.1255±0.0003mm, the inner diameter tolerance was ≤0.3μm, the concentricity was ≤0.5μm, the bending strength was ≥500MPa, and the thermal expansion coefficient was 4.2×10 -6 / ℃.

[0048] Example 2 Preparation of glass-ceramic core by bulk crystallization method The preparation process of this embodiment is roughly as follows Figure 2 As shown, the details are as follows: (1) Raw material selection and preparation According to the performance requirements of the required microcrystalline glass, appropriate amounts of SiO2, Al2O3, Li2O, etc. are selected as glass formers, among which the SiO2 content is 50wt%, the Al2O3 content is 25wt%, and the Li2O content is 15wt%; 1.5 wt% ZrO2 and 0.4wt% P2O5 are selected as nucleating agents, and 2 wt% SnO2 is added as a clarifier, 4wt% K2O and 2wt% Na2O are added as fluxes, and 0.1wt% ZnO is used as a strength additive to ensure the purity and proportion of the raw materials.

[0049] (2) Melt molding The prepared raw materials are placed in a high-temperature furnace and heated to 1600℃±5℃ to completely melt the raw materials to form a uniform glass liquid. Subsequently, the initial shape of the ferrule is obtained by pouring or pressing through a precision mold. In this process, the melting temperature and holding time must be strictly controlled to ensure the uniformity and fluidity of the glass liquid.

[0050] (3) Overall crystallization treatment The preliminarily formed insert is placed in a precisely controlled heat treatment furnace for overall crystallization treatment. First, the nucleation treatment is carried out at 570℃±5℃ for 2h to form a large number of crystal nuclei inside the glass; then the crystallization treatment is carried out at 800℃±5℃ for 2h to make the crystal nuclei grow into fine crystal phases, forming a microcrystalline glass insert with the required properties.

[0051] (4) Precision machining The core insert after overall crystallization treatment is precisely ground and polished to remove surface defects and tiny cracks to ensure that its dimensional accuracy meets the requirements.

[0052] (5) Performance testing The prepared microcrystalline glass optical fiber ferrule was tested. The outer diameter of the ferrule was 2.499±0.0002mm, the outer diameter tolerance was ≤0.2μm, the inner diameter was 0.1255±0.0002mm, the inner diameter tolerance was ≤0.2μm, the concentricity was ≤0.4μm, the bending strength was ≥450MPa, and the thermal expansion coefficient was ≤3.5×10 -6 / ℃.

[0053] Comparative Example 1 The thermal expansion coefficient is 8.2×10 -6 / ℃ finished ZrO2 ceramic ferrule.

[0054] Verification Example 1 High temperature resistance and thermal shock resistance test The samples of Example 1, Example 2, and Comparative Example 1 were rapidly heated to 500°C at a rate of 10°C / min (maintained for 30 minutes), quickly placed in 20°C cooling water for quenching (maintained for 10 seconds), taken out and dried at 110°C for 2 hours, and then cooled to room temperature to test the residual bending strength of the microcrystalline glass optical fiber ferrule. Then, they were heated to 600°C, 700°C, 750°C, 800°C, and 1100°C for testing, and the results are shown in Table 1.

[0055] Table 1 High temperature resistance and thermal shock resistance test of Example 1, Example 2 and Comparative Example 1

[0056] From Table 1, it can be calculated that the maximum allowable temperature difference ΔT of Example 1 and Example 2 are 673.63°C and 692.11°C respectively, and no microcracks or damage are produced on the surface of the sample when heated to 1100°C. The maximum allowable temperature difference ΔT of Comparative Example 1 is 484.50°C, and when heated to 1100°C, microcracks are produced on the surface. This is because during the continuous heating and thermal shock performance test, the ZrO2 ceramic undergoes a phase change, producing a large amount of monoclinic phase, resulting in volume changes, thereby generating thermal stress, and then causing cracking. Therefore, it is shown that compared with the comparative example, the prepared microcrystalline glass core in the embodiment of the present application has stronger resistance to high and low temperature cycle impact and thermal shock than the ceramic core, and can withstand higher temperatures, and has better stability in high temperature environments.

[0057] Verification Example 2: Assembly and testing of optical fiber connectors (1) Preparation of parts: Based on the glass-ceramic ferrule prepared in Example 2 and the ceramic ferrule of Comparative Example 1, single-mode optical cables (8.3 / 125 μm) and optical fiber connector parts are also prepared. The optical fiber needs to undergo pre-processing steps such as cutting, grinding and cleaning to ensure that its end face is flat and free of defects.

[0058] (2) Assembly process: Cut the aramid fiber at a distance of 1 to 2 mm from the metal tail handle of the sleeve; insert the fiber optic connector parts such as the tail sleeve, retaining ring, external screw, and spring in order; insert the ferrule into the inner sleeve and push it in for fixed installation; insert the pre-treated optical fiber into the hole of the microcrystalline glass ferrule, ensure that the optical fiber is coaxial with the ferrule and the end faces are in close contact, and fix it with glue; fix the aramid fiber and the sheath, and push the tail sleeve into the limit groove to complete the installation of the tail sleeve; then put the SC type outer sleeve on the ferrule, and push the tail sleeve and inner sleeve hard to complete the installation of the SC outer sleeve. The above process ensures the stable connection of the optical fiber in the connector; a total of six samples were made, named samples 1-6.

[0059] (3) Inspection and testing: After the single-mode SC fiber optic connector is assembled, the ferrule end face is polished in multiple steps to form a PC-type contact. The assembly effect and ferrule end face quality of the fiber optic connector are inspected. The ferrule has appropriate elasticity, no cracks on the end face, and the gap between the ferrule and the sleeve is uniform and symmetrical. The SC jacket can move freely when pulled. The fiber optic connector is tested for performance, including insertion loss test and return loss test.

[0060] The test results of Example 1 and Comparative Example 1 are shown in Table 2. Table 2 Fiber optic connector performance test

[0061] It can be seen from Table 2 that the maximum insertion loss of the single-mode SC / PC optical fiber connector of Example 2 is ≤0.18dB@1310nm, and the minimum return loss is ≥58dB@1310nm.

[0062] The formula of the microcrystalline glass core of the optical fiber connector was adjusted, including adjusting the proportion of the basic component SiO2 between 50 wt% and 80 wt%, the proportion of Al2O3 between 5 wt% and 40 wt%, and the proportion of Li2O between 8 wt% and 30 wt%. It was found that the performance of the optical fiber connector was not greatly affected, and the test parameters of the produced optical fiber connector were roughly equivalent to those of Example 1 and Example 2; the proportions of auxiliary components other than the strength additive were adjusted, for example, the nucleating agent was between 0.5 wt% and 7 wt%, the clarifying agent was between 0 wt% and 3 wt%, and the flux was between 1 wt% and 6 wt%, and it was found that the performance of the optical fiber connector was not affected; in addition, the specific compounds used in the auxiliary components have negligible effects on the performance of the optical fiber connector.

[0063] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. An application of microcrystalline glass in an optical fiber ferrule, characterized in that: The microcrystalline glass includes 50 wt%~80wt% of SiO2, 5wt%~40wt% of Al2O3, 8wt%~30wt% of Li2O and 0.1wt%~3wt% of strength additives; the strength additives are one or more of rare earth metal compounds, transition metal compounds, organic fibers, silicon nitride fibers, borates, phosphates, magnesium oxide, and magnesium fluoride.

2. The use according to claim 1, characterized in that The strength additive is ZnO or MgO.

3. The use according to claim 1, characterized in that The microcrystalline glass also includes 0.5 wt% to 7 wt% of a crystal nucleating agent, 0 wt% to 3 wt% of a clarifier and 1 wt% to 6 wt% of a flux.

4. The use according to claim 3, characterized in that The crystal nucleating agent is one or more of ZrO2, TiO2, P2O5, SnO2, and Nb2O5.

5. The use according to claim 3, characterized in that The clarifier is one or more of Na2SO4, Sb2O3, and SnO2.

6. The use according to claim 3, characterized in that The flux is one or more of Na2O, MgO, K2O, B2O3, and ZnO.

7. The use according to claim 1, characterized in that The thermal expansion coefficient of the optical fiber ferrule is less than 5×10 -6 / ℃, the maximum allowable temperature difference is greater than 600℃.

8. The use according to claim 1, characterized in that The microcrystalline glass is prepared by a sintering method or a bulk crystallization method.

9. An optical fiber ferrule, characterized in that: The material of the optical fiber core is microcrystalline glass, which includes 50 wt%~80wt% SiO2, 5wt%~40wt% Al2O3, 8wt%~30wt% Li2O and 0.1wt%~3wt% strength additives; the strength additives are one or more of rare earth metal compounds, transition metal compounds, organic fibers, silicon nitride fibers, borates, phosphates, magnesium oxide, and magnesium fluoride.

10. An optical fiber connector comprising the optical fiber ferrule according to claim 9.

Citation Information

Cited By

  • Glass ceramic composite optical fiber as well as preparation method and application thereof

    CN121779005A